Creep behaviour of steel P23 weldments. (31st May 2011) - Vlasak, Tomas; Hakl, Jan; Brziak, Peter; Bernasovsky, Peter; , Jozef Pecha
Low-alloy creep resistant steel P23 (2.25%Cr-1.6%W-0.25%V) has been developed for pipelines in power engineering. Creep resistance of this steel was already evaluated. Continuation of this work is the investigation of possibilities of weldment production. This paper reports some of this possibilities and mentioned further are the creep strength and metallographic evaluation of the optimally prepared weldments P23 – P23.